A Comparative Study on Growth and Metabolism of Eriocheir sinensis Juveniles Under Chronically Low and High pH Stress - Wang, Xiaodan; Huang, Zhipeng; Wang, Chunling; Qi, Changle; Gu, Zhimin; Li, Erchao; Qin, Jian G.; Chen, Liqiao (Frontiers in Physiology, 2020)
This study elucidates the effects of chronic pH stress on the growth and metabolic response of juvenile Chinese mitten crab Eriocheir sinensis. Crabs were exposed under normal pH (control, pH = 8.0 ± 0.20), low pH (pH = 6.5 ± 0.20) and high pH (pH = 9.5 ± 0.20) in an 8-week trial. Both low and high pH suppressed weight gain but low pH had more adverse effects. No difference was observed on survival, crude lipid and protein. Acidic stress significantly reduced protein efficiency. The malonaldehyde content in hepatopancreas was highest at low pH. The superoxide dismutase activity in hepatopancreas and total hemocyte counts in the stress groups were higher than that in the control. Crabs under high pH had the highest ACP and AKP activities, but there was no significant difference between the control and low pH groups. In the transcriptome analysis, 500.0 M clean reads were obtained from the control, low pH and high pH groups, and assembled into 83,025 transcripts. KEGG pathways were analyzed to obtain the significantly changed pathways involving differently expressed genes. Ten and eight pathways in metabolism were significantly changed in low pH vs control and high pH vs control groups, respectively. According to the reported functions of these pathways, most of them participated in carbohydrate metabolism. The metabolism pathway analysis indicates the increases of stress resistance, glucose metabolism and molting activities under chronically pH stress. This study suggests that low pH has more negative impact on crab growth, and oxidative phosphorylation is the main source of energy source under low pH stress, while aerobic glycolysis supplies most energy under high pH stress.